2015
DOI: 10.1038/srep15256
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fiber prevents obesity-related liver lipotoxicity by modulating sterol-regulatory element binding protein pathway in C57BL/6J mice fed a high-fat/cholesterol diet

Abstract: Adequate intake of dietary fibers has proven metabolic and cardiovascular benefits, molecular mechanisms remain still limited. This study was aimed to investigate the effects of cereal dietary fiber on obesity-related liver lipotoxicity in C57BL/6J mice fed a high-fat/cholesterol (HFC) diet and underlying mechanism. Forty-eight adult male C57BL/6J mice were randomly given a reference chow diet, or a high fat/choleserol (HFC) diet supplemented with or without oat fiber or wheat bran fiber for 24 weeks. Our resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
64
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 49 publications
8
64
0
8
Order By: Relevance
“…The degenerative changes in the histology of liver of STZ-induced type 2 diabetic ICR mice were similar to previous observations [Teoh et al, 2008]. Histologically, liver section of STZ--induced diabetic mice showed severe degeneration, necrosis, hepatocellular swelling, infl ammatory cell infi ltrate and a lot of large lipid droplets in the cytoplasm and those symptoms were strongly correlated with insulin resistance [Han et al, 2015]. This damage was partially reversed by feeding okara and soybean bran and was similar to an observation that soybean treatment decreased the pathogenic effect and removed the fatty change in liver of diabetic rats [Amer, 2012].…”
Section: Discussionsupporting
confidence: 89%
“…The degenerative changes in the histology of liver of STZ-induced type 2 diabetic ICR mice were similar to previous observations [Teoh et al, 2008]. Histologically, liver section of STZ--induced diabetic mice showed severe degeneration, necrosis, hepatocellular swelling, infl ammatory cell infi ltrate and a lot of large lipid droplets in the cytoplasm and those symptoms were strongly correlated with insulin resistance [Han et al, 2015]. This damage was partially reversed by feeding okara and soybean bran and was similar to an observation that soybean treatment decreased the pathogenic effect and removed the fatty change in liver of diabetic rats [Amer, 2012].…”
Section: Discussionsupporting
confidence: 89%
“…Sharma (2002) showed that potato peels have shown that it might have therapeutic activity to its high content in dietary fiber as hypercholesterolemia. Also, this result is in accordance with Han et al (2015).In case of AST and ALT as liver functions, the data presented in the table (7) show that the levels of AST and ALT in the rat's serum were within normal limits under the administration of different dietary fiber sources.Sodium and copper as important elements were significantly decreased when dietary fiber cake sources were added to diet's rats (table 8). There were no differences between positive and negative control.…”
supporting
confidence: 74%
“…Southgate et al [14] reported that dietary bran reduces nutrient absorption. Seminal studies performed by Han et al [11] demonstrated that WB increases the expression of proteins related to fatty acid oxidation by modulating the sterol-regulatory element binding protein pathway, and increases lipolysis and browning of adipocytes [12] in mice. On the other hand, many studies have demonstrated that chronic disruption and suppression of GIP signaling, either genetically, or by vaccination against GIP, or by administration of materials that reduce postprandial blood GIP, leads to high fat utilization and accelerates lipolysis in adipose tissue [2125,2729,34].…”
Section: Discussionmentioning
confidence: 99%
“…Wheat bran (WB) is the outer covering of the wheat grain, and contains abundant vitamins, minerals, and DF [10]. Chronic consumption of WB effectively improves obesity in mice [11,12]. Han et al [11] demonstrated that chronic feeding with WB induces the expression of proteins involved in fat oxidation and suppresses the expression of proteins involved in fatty acid synthesis in liver and epididymal adipose tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation